PARADIGMA MAZHAB POSITIVISME HUKUM TERHADAP KETIDAKSESUAIAN NAMA KOPERASI DALAM SISTEM ADMINISTRASI BADAN HUKUM (SABH) KEMENTERIAN HUKUM DENGAN AKTA KOPERASI - Felly Faradina; Zulhendrawan (Desiderata Law Review, 2025)
The name of a Cooperative stated in its deed should match the name registered in the Legal Entity Administration System (SABH), so that the decree on the ratification or registration of amendments to the articles of association reflects the name in the deed. However, in practice, discrepancies often arise where the Cooperative’s name in the notarial deed differs from the name listed in SABH. This results in the issuance of a decree under a different name than that in the original deed. This study examines the Legal Positivism School's paradigm regarding the inconsistency of Cooperative names between SABH of the Ministry of Law and the notarial deed. The research uses a normative-sociological legal method, applying statutory, comparative, and historical approaches, and drawing on both primary and secondary data. The study finds that such discrepancies create legal issues for Cooperatives as legal subjects, particularly in relation to the validity of notarial deeds. This inconsistency can affect the legal recognition of the Cooperative's status, the validity of agreements with third parties, the legitimacy of its management, and may lead to legal disputes. From the perspective of Legal Positivism, this name mismatch is seen as a violation of formal legal norms. This paradigm emphasizes formal legality and procedural correctness without considering moral or social objectives beyond written norms. Therefore, the legal solutions must focus on regulatory reform, administrative system improvement, and consistent application of positive law